Toward High‐Throughput Texturing of Polymer Foils for Enhanced Light Trapping in Flexible Perovskite Solar Cells Using Roll‐to‐Roll Hot Embossing. Issue 4 (9th January 2020) - Soldera, Marcos; Wang, Qiong; Soldera, Flavio; Lang, Valentin; Abate, Antonio; Lasagni, Andrés Fabián
Abstract : A path to further increase the power conversion efficiency of perovskite solar cells is maximizing sunlight absorption using patterned substrates with enhanced light‐trapping capabilities. However, to be competitive with traditional solar cells, especially in niche markets, low‐cost texturing methods have to be developed. Herein, a roll‐to‐roll hot embossing method to pattern flexible polyethylene terephthalate (PET) foils is presented as a proof of concept. The cylindrical mold for the embossing process is structured with periodic grooves by picosecond direct laser interference patterning (DLIP). The optical characterization of the textured PET shows a tenfold increase in the haze factor (diffuse‐to‐global transmittance ratio) compared with flat PET due to the high‐intensity diffracted beams. Flexible triple cation perovskite cells deposited onto these patterned substrates show on average an 8% (relative) higher efficiency than similar devices deposited on a reference flat PET substrate. This enhancement can be attributed to the increase in light trapping provided by the textured substrate. Finally, a cost analysis model shows that the additional cost of integrating the proposed hot embossing step into a perovskite solar module manufacturing facility will represent less than 0.35% of the initial fabrication cost. Abstract : A high‐throughput method is presented to texture polymer foils by roll‐to‐roll hot embossing with the objective of increasing the substrate haze factor. Triple cation perovskite solar cells are deposited onto these structured substrates, showing an efficiency increase up to 15% (relative) compared with the reference flat device, due to an enhanced light absorption.